Synergistic antimicrobial therapy using nanoparticles and antibiotics for the treatment of multidrug-resistant bacterial infection. Issue 1 (2nd May 2017) - Gupta, Akash; Saleh, Neveen M; Das, Riddha; Landis, Ryan F; Bigdeli, Arafeh; Motamedchaboki, Khatereh; Rosa Campos, Alexandre; Pomeroy, Kenneth; Mahmoudi, Morteza; Rotello, Vincent M
Abstract: Infections caused by multidrug-resistant (MDR) bacteria pose a serious global burden of mortality, causing thousands of deaths each year. Antibiotic treatment of resistant infections further contributes to the rapidly increasing number of antibiotic-resistant species and strains. Synthetic macromolecules such as nanoparticles (NPs) exhibit broad-spectrum activity against MDR species, however lack of specificity towards bacteria relative to their mammalian hosts limits their widespread therapeutic application. Here, we demonstrate synergistic antimicrobial therapy using hydrophobically functionalized NPs and fluoroquinolone antibiotics for treatment of MDR bacterial strains. An 8–16-fold decrease in antibiotic dosage is achieved in presence of engineered NPs to combat MDR strains. This strategy demonstrates the potential of using NPs to 'revive' antibiotics that have been rendered ineffective due to the development of resistance by pathogenic bacteria.